Bimetallic Heterogeneous Catalysis for Oxygen Evaluation Reaction with Varying Concentrations of Silica - Singh C.; Singh K. (My University, 2025)
Although the effectiveness of noble metal nanocatalysts per noble metal atom is currently low, they are frequently used in heterogeneous catalysis. Nanostructured silica is necessary for the recyclability of nanocatalysts, the synergistic interaction of bimetallic components during OER, and the much enhanced palladium nanogeometry. Co-NTA nanowires were used as a precursor in the synthesis of Co@Pdnps, which was mediated by organotrialkoxysilane to regulate the existence of nanostructured silica after calcination that is helpful in OER, Co@Pdnps were created employing a variable amount of organotrialkoxysilane in an N-doped carbon matrix. They were then examined by XRD, TEM, and EDX. With a small Tafel slope of 39 mV dec−1, a catalyst loading of 2 mg cm−2, and a nanostructured silicon-derived thin film constituted of Co@Pdnps, a very high current density was obtained at a low overpotential. In the absence of silica, the nanocatalysts are somewhat bigger and exhibit a lower current density (20.5 mA cm−2) than those that were seen with a high silica concentration. © 2023, The Author(s), under exclusive license to Springer Nature Singapore Pte Ltd.